Penyusunan Portofolio Kampung Pendidikan Arek Surabaya - Yesa Cahayaning; Asmara Indahingwati (Universitas Lancang Kuning, 2021)
Parenting patterns depend on how a family environment forms rules (behavior, norms and values) that must be obeyed by family members. This parenting pattern is formed by parents consisting of fathers and mothers to provide education to their children so that it can imprint on the child and make characteristics and personal for the child. So the mayor of Surabaya held the Kampung'e Arek Suroboyo education village competition which was one of the Surabaya City Government's programs in promoting the development of the quality of human resources (HR). Thus mandating